The Legal Framework of Public Service - Adel Abdul Sahib, Assist. Lect. Inas (Basra studies journal, 2026)
Institutions, as it contributes to the implementation of public policies, the provision of services, and the achievement of administrative objectives. It is not merely a paid occupation but a legal position governed by rules regulating the relationship between employees and the state in terms of rights and obligations. The legal framework governing public service is central to this relationship, defining the principles of appointment, promotion, discipline, and the guarantees afforded to employees in their interactions with the administration. The importance of studying this relationship arises from the need to analyze legal texts, judicial applications, and relevant scholarly opinions in light of administrative and legislative developments. This research examines the legal organization of public service and highlights the distinctive nature of the relationship between employees and the public administration, in contrast with the private sector. The study concludes that this relationship is both organizational and legal in nature, requiring continuous development of the legislative framework through the analysis of statutes, principles, and practical realities, in order to maintain a balance between the interests of the administration and the rights of public employees.